Intentional control of invasive mobile wireless systems - Ponte, João Pedro de Castro (2020)
Within recent years, remotely operated or autonomous drones have been encroaching on the realm of consumer electronics and are beginning to crowd the airspace in populated areas. As such, the number of incidents involving drones has seen a sharp increase and concerns are being raised. In this sense, the current work aims to explore a method which enables spoofing of the Global Positioning System (GPS) many of these devices use to navigate, and thus provide a way to shift them off course and away from the intended areas. The proposed hypothesis is that, by altering the parameters by which GPS receivers correct for clock errors in the navigation systems, it is possible to shift the device’s perceived position in a measurable and easily replicable way. To test this hypothesis, a simulator was developed to test different offsets applied to the clock correction coefficients of a GPS navigation message. The positions resulting from calculations using these altered parameters were then plotted on a map of the surrounding area and analysed. As expected, the positions are effectively and predictably altered according to the offsets applied. In order to validate the results from the simulations, real world tests were conducted using a Software Defined Radio (SDR) platform and an open source GPS Signal Generator which was modified to generate a signal based on the altered data from the simulations. With these tests it was asserted that the spoofed signals were able to consistently cause receivers to miscalculate their positions analogously to the simulations.